Diferentes diâmetros de gotas e equipamentos para aplicação de inseticida no controle de Pseudoplusia includens - di Oliveira, Jose R. G. [UNESP]; Ferreira, Marcelo da C. [UNESP]; Roman, Rodrigo A. A. (Soc Brasil Engenharia Agricola, 2010)
It was aimed to evaluate the spectrum and uniformity of droplets in function of sprayers, spraying volumes and rates of chemical insecticide on the mortality of Pseudoplusia includens in laboratory. The work was carried out at UNESP, Jaboticabal, SP, Brazil. The following treatments were applied over the caterpillars: two equipments (atomizer and hydraulic nozzle); two spray volumes (17 and 50 L ha(-1) for the atomizer and 50 and 100 L ha(-1) for the hydraulic nozzle); and two dosages of the insecticide endosulfan (0.5 and 1.0 L pc ha(-1)), in fully randomized plots, in a factorial scheme 2x2x2 and 1 untreated check. The caterpillars mortality was evaluated until the 6(th) day after the application of treatments. The spectrum of the droplets was evaluated in a particle size analyzer in real time determining the diameter and spectrum of droplets sprayed through the laser beam of the analyser. It was verified that the spray volume can be reduced by 17 L ha(-1) without losses on the P. includens control. The doses of 0.5 L pc ha(-1) (recommended for Anticarsia gemmatalis) did not satisfactorily control the caterpillar soybean looper. The atomizer produces droplets of higher uniformity (SPAN: 0.52) and lower percentage of droplets susceptible to drift (3.3%) compared to hydraulic nozzle (SPAN: 1.34 e % droplets <= 100 mu m: 15.2).
Diameter of droplets and different equipments for the application of insecticide to control pseudoplusia includes
Keywords: atomizer; droplet spectrum; Soybean looper